Synthesis and Characterization of Polymeric Surfactant from Palm Oil Methyl Ester and Vinyl Acetate for Chemical Flooding - Agam Duma Kalista Wibowo; Pina Tiani; Lisa Aditya; Aniek Sri Handayani; Marcelinus Christwardana (Dept. of Chemical Engineering, Diponegoro University, 2021)
Surfactants for enhanced oil recovery are generally made from non-renewable petroleum sulfonates and their prices are relatively expensive, so it is necessary to synthesis the bio-based surfactants that are renewable and ecofriendly. The surfactant solution can reduce the interfacial tension (IFT) between oil and water while vinyl acetate monomer has an ability to increase the viscosity as a mobility control. Therefore, polymeric surfactant has both combination properties in reducing the oil/water IFT and increasing the viscosity of the aqueous solution simultaneously. Based on the study, the Critical Micelle Concentration (CMC) of Polymeric Surfactant was at 0.5% concentration with an IFT of 7.72x10-2 mN/m. The best mole ratio of methyl ester sulfonate to vinyl acetate for polymeric surfactant synthesis was 1:0.5 with an IFT of 6.7x10-3 mN/m. Characterization of the product using FTIR and HNMR has proven the creation of polymeric surfactant. Based on the wettability alteration study, it confirmed that the product has an ability to alter from the initial oil-wet to water-wet quartz surface. In conclusion, the polymeric surfactant has ultralow IFT and could be an alternative surfactant for chemical flooding because the IFT value met with the required standard for chemical flooding ranges from 10-2 to 10-3 mN/m.Keywords: Enhanced Oil recovery, Interfacial Tension, Methyl Ester Sulfonate, Polymeric surfactant, vinyl acetate